El rescripto de Antonino Pío sobre los esclavos de Iulius Sabinus de la Bética - González Roman, Cristóbal (Gerión. Revista de Historia Antigua, 2003)
Antoninus Pius’ s rescriptum on the slaves of Iulius Sabinus is an exceptional document pertaining to slavery in the Betica province. lts contents regulate the slave shelter in the temple devoted to the worship of the emperor.